Chemical, biological and in silico assessment of date (P. dactylifera L.) fruits grown in Ha’il region - Alsukaibi, Abdulmohsen Khalaf Dhahi; Alenezi, Khalaf M.; Haque, Ashanul; Ahmad, Irfan; Saeed, Mohd; Verma, Mahima; Ansari, Irfan Ahmad; Hsieh, Ming-Fa (Frontiers in Chemistry, 2023)
Background: Dates palm (Phoenix dactylifera L.) fruits are among the most widely used fruits in the Middle East and African nations. Numerous researchers confirmed the presence of phytochemicals in P. dactylifera L. fruit and its by-products with broad-ranging biological activities. Objectives: In the present work, phytochemical and biological assessments of two different cultivars of date fruit (ShishiM1 and MajdoolM2 grown in the Ha’il region of Saudi Arabia) have been carried out. Methods: Date fruits were extracted and analyzed by gas chromatography-mass spectrometry (GS-MS),liquid chromatography-mass spectrometry (LC-MS) and Fourier-transform infrared spectroscopy (FT-IR)techniques. The lyophilized methanolic extracts were analyzed for their in-vitro antiproliferative andcytotoxicity against colon cancer (HCT116) cell line. To identify the possible constituents responsible for the bioactivity, in-silico molecular docking and molecular dynamics (MD) simulation studies were carried out. Results: Both cultivars exhibited in-vitro anticancer activity (IC50 = 591.3 μg/mL and 449.9 μg/mL for M1 and M2, respectively) against colon cancer HCT-116 cells. The computational analysis results indicated procyanidin B2 and luteolin-7-O-rutinoside as the active constituents. Conclusion: Based on these results, we conclude that these cultivars could be a valuable source for developing health promoter phytochemicals, leading to the development of the Ha’il region, Saudi Arabia.